Failure of Placental Detachment in Accreta Placentation is Associated With Excessive Fibrinoid Deposition at the Utero-placental Interface. Issue 4 (21st December 2022) - Jauniaux, E.; Hussein, A.M.; Elbarmelgy, R.M.; Elbarmelgy, R.A.; Burton, G.J.
Abstract : ( Am J Obstet Gynecol . 2022;226:243.e1–10) Since placenta accreta was first described in 1937, the condition has been diagnosed by the direct attachment of villous tissue to the superficial myometrium or adjacent fibers without interposing decidua. There has been a lack of histopathologic studies investigating placenta accreta spectrum (PAS) disorders. This study aimed to evaluate the microscopic changes used to determine the grade of PAS and identify possible explanations of the abnormal placental tissue attachment in patients with scars from previous cesarean delivery.